Men in the margins a content analysis of news coverage of transgender men in INQUIRER.net, Rappler and GMANetwork.com - Apostol, Liana Bettina D.
Amid a generational shift in improving storytelling of marginalized communities, transgender men have had less exposure in the media compared to other sectors in the LGBTQ+ community. This study used content analysis to examine the representation of transgender men in mainstream Philippine digital news outlets to understand how Philippine media covers, frames, and legitimizes transgender men in their storytelling. Using Robert Entman’s framing theory, Daniel Hallin’s spheres of legitimate controversy and deviance, Holli Semetko and Patti Valkenburg’s news frame categorizations and Thomas Billard’s legitimacy indicators, this study found that mainstream coverage of transgender men is scarce, with most of the exposure dedicated to transgender men with existing celebrity status.